Electroanalysis in biomedical and pharmaceutical sciences : voltammetry, amperometry, biosensors, applications /: voltammetry, amperometry, biosensors, applications. (2015) - Ozkan, Sibel A; Kauffmann, Jean-Michel; Zuman, Petr
No abstract available